The Effect of Family Support in Nutrition Education on Dietary Adherence and Blood Glucose Levels of Type 2 Diabetes Mellitus Inpatients at Panti Rapih Hospital Yogyakarta - Setyaning Jati, Yacinta Adies; Setyaji, Diyan Yunanto; Purnawijayanti, Hiasinta Anatasia (Journal of Global Nutrition, 2024)
Diabetes mellitus is included in the group of metabolic diseases with characteristics of hyperglycemia that occurs due to abnormalities in insulin secretion and function or both. According to the Association of Diabetes Care and Education Specialists, there are 7 pillars of diabetes mellitus management that can be done, one of which is providing nutritional education. The purpose of this study was to determine an effect of family support in nutritional education on dietary compliance and blood glucose levels of type 2 diabetes mellitus at Panti Rapih Hospital, Yogyakarta. This study used a quantitative research design with a quasy experiment design with an accidental sampling method with a sample size of 34 diabetes mellitus inpatients divided into control and experimental groups. The variables of this study will be analyzed using SPSS, with the T-Paired Test and T-Independent Sample Test. Based on the statistical results, the effect of education on dietary compliance in the control and experimental groups showed a p value of 0.000 <0.05. While the statistical results of the effect of education on blood glucose levels in the control group showed a p value of 0.002 <0.05, in the experimental group the results of the p value were 0.001 <0.05. However, based on the results of the statistical test on the difference in compliance scores, a p value of 0.000 <0.05 was obtained. While the results of the statistical test of blood glucose levels obtained a p value of 0.315> 0.05. It can be concluded that family support in providing nutritional education can influence the increase in compliance scores for following a diet but does not affect blood glucose levels in type 2 diabetes mellitus patients at Panti Rapih Hospital, Yogyakarta.